Computer Based Design and Manufacturing - Nasr, Emad Abouel. (Springer US : Imprint: Springer, 2007)
"Computer- Based Design and Manufacturing" offers insights into the methods and techniques that enable implementing a product design philosophy by integrating capabilities for intelligent information support and group decision-making utilizing a common enterprise network model and knowledge interface through shared technologies. This book offers a comprehensive overview of the latest methods and state-of-the-art technologies in intelligent product design. Including but not limited to: - Discussion of applied methods developed in field of the product design - Discussion on the need and solutions for new engineering paradigm and philosophy required for product design - Coverage of advances in information systems and technology in support of CFPD - Discussion of how to use web-based design environments "Computer-Based Design and Manufacturing" is a must have book for industrial engineers in both industry and academia who specialize in product development and supply chain management.